B-ISDN connection admission control and routing strategy with traffic prediction by neural networks - Neves, Joaquim José Santos Esteves (1994)
The resource allocation in the Broadband Integrated Services Digital Network (B-ISDN) can be based in an overall network performance function described in this paper and named quality of operation. The quality of operation function is determined itself by bandwidth and quality of service functions. The traffic patterns of the quality of service for each call are predicted by neural networks. The applicability of the quality of operation function to connection admission control and call routing is proposed and supported by simulation results.